(untitled) (Bangladesh Journal of Agricultural Research, 2023)
An experiment was conducted at the Floriculture Shade Net House under Horticulture Research Centre of Bangladesh Agricultural Research Institute, Gazipur during 2020-21 to evaluate the effect of different substrates on growth, flowering, yield and quality of anthurium. Six treatments were used viz,. T1: Soil (control), T2: Cocodust, T3: Perlite, T4: Sawdust, T5: Cocodust + Perlite (1:1), and T6: Cocodust + Sawdust (1:1). The experiment was laid out in Completely Randomized Design with five replications. The result showed that Cocodust + perlite (1:1) followed by Cocodust singly performed the best in respect of growth, flower number and quality characteristics of anthurium. Poor performance of all characteristics of anthurium was exhibited in control treatment. Gross return and BCR was the highest in T5 treatment. The result suggested that Perlite + Cocodust (1:1 ratio) followed by Cocodust (100%) could be used for flower yield maximization and quality improvement of anthurium in pot cultivation. Bangladesh J. Agril. Res. 46(4): 435-443, December 2021